The changing role of English in Bangladesh - Mohammad Mosiur Rahman (Peoples' Friendship University of Russia (RUDN University), 2022)
The importance of English as the dominant global language, the language of communication, technology, academia, economics, and entertainment is undeniable. Based on the steady economic growth throughout the country during the previous decade, Bangladesh was classified as a lower middle-income nation in a report published by the World Bank in 2016. Given these facts, it is undisputed that English plays an essential role in ensuring the continuation of economic development and the cultivation of skilled labour force that is compatible with international standards and highly demanded to meet the local needs of the employers. The purpose of this article is to situate the case of Bangladesh among other contexts of English as a foreign language (EFL) and English as a lingua franca (ELF) with reference to the (dis)similarities between language policy and planning-related events. The article provides a detailed understanding of the language policy and planning of Bangladesh as a postcolonial society. Although Bangladesh had embraced a nationalistic approach after its independence, the discussion of this study highlighted recent changes in the English language policy initiatives in the country and the increasing use of English in different domains. The current emergence of English in Bangladesh resulted from internal and external forces, needs, and aspirations.